2022
DOI: 10.1155/2022/3237639
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preprocessing Storage Temperature and Time on the Physicochemical Properties of Winter Melon Juice

Abstract: Numerous studies demonstrated that winter melons (Benincasa hispida) have a long storage life at 20°C without quality and flavor degradation in fruit. However, fruit for processing are frequently handled under refrigerated conditions or exposed to a warehouse without air conditioning. Therefore, this research aimed to evaluate whether a short high- and low-temperature storage of fruit, prior to processing, changes the flavor and nutritional profiles of winter melon juice. Weight loss of 1.71% was recorded subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Typically, fruit are stored in cold temperatures for extended periods of time. However, similarly to other chilling sensitive fruit, such as mango [26] and Japanese apricot [27], winter melons suffer chilling injury when stored below 13 • C [15,28,29]; therefore room temperature is recommended for long-term storage [15]. A long-term storage experiment showed that many winter melon breeding lines could be stored at ambient temperature up to 120 d [30].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, fruit are stored in cold temperatures for extended periods of time. However, similarly to other chilling sensitive fruit, such as mango [26] and Japanese apricot [27], winter melons suffer chilling injury when stored below 13 • C [15,28,29]; therefore room temperature is recommended for long-term storage [15]. A long-term storage experiment showed that many winter melon breeding lines could be stored at ambient temperature up to 120 d [30].…”
Section: Introductionmentioning
confidence: 99%
“…For example, heat treatment changes the aroma profiles of melons, causing a reduced "fresh" aroma as well as increased unpleasant "sulfurous" and "fermented" aroma (Yu et al, 2021). Additionally, total volatiles in melon juice are reduced significantly after 10°C storage for 20 d (Sun et al, 2022). In tomato, chilling results in loss of fruit flavor through impacting various flavor-associated VOCs (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Bligo juice has been added with various sugars and stabilizers (such as CMC) and subjected to different treatments to increase its physiochemical and functional properties. However, the use of Bligo Peel Extract (BPE) to increase the functional value of bligo juice has not been explored, except for Sun et al (14) who prepared bligo juice without removing the peel but did not examine the effectiveness of bligo peel in enhancing functional properties. Therefore, the current research was conducted to investigate the effect of BPE addition on the physicochemical, antioxidant activity, and sensory attributes of bligo juice.…”
Section: Introductionmentioning
confidence: 99%